Supervision of construction proceedings of a symposium organized by the Institution of Civil Engineers and held in London, 7-8 June 1984. (Thomas Telford, 1985)
Focusing on supervision in construction, these papers discuss the role of the engineer, the engineer's representative, the contractor, and site agent, and provide a supervision brief.
Keywords: Construction industry -- Management -- Congresses.; elektronické knihy; electronic books